Utilization of Sansevieria As a CO and HC Exhaust Gas Filter in Motorized Vehicles in Preventive Climate Change Efforts - Agung, Tri Sunan; Zuhri, Belinda Safa Salsabila; Suprayogi, Dedy (International Conference on Sustainable Health Promotion, 2023)
Motor vehicle emissions cause air pollution, such as: CO and HC gases. These two gases cause climate change and pose threats to human health, such as poisoning, and cancer. Sansevieria sp. is a plant that can absorb 107 pollutants in the air such as carbon monoxide, formaldehyde, and trichlorethylene. Based on this potential, researchers innovate to make filters based on sansevieria. This study examines the effectiveness of filtering CO and HC gases after installing filters in motorized vehicles. This research method uses a quantitative descriptive with an experimental approach. The independent variable is the composition of the number of filters and gels, while the dependent variable is the effectiveness of reducing HC and CO levels. Filter testing using a gas analyzer with a motorcycle engine speed from 1500 RPM to 9000 RPM. The results of this study showed that CO and HC emissions after being treated in sample A from 1500 RPM to 9000 RPM showed a reduction of 67% CO and 25% HC. Meanwhile, in sample B, the decrease in CO was 80% and HC was 51%. The ability of the sansevieria filter to reduce CO and HC gas emissions can be a climate change prevention effort, because it can reduce the potential for GHG due to motorized vehicles